Fixed Point of a New Three-Step Iteration Algorithm under Contractive-Like Operators over Normed Spaces - Karakaya, Vatan; Dogan, Kadri; Gursoy, Faik; Erturk, Muzeyyen (HINDAWI LTD, 2013)
We introduce a new three-step iteration scheme and prove that this new iteration scheme is convergent to fixed points of contractive-like operators. Also, by providing an example, we show that our new iteration method is faster than another iteration method due to Suantai (2005). Furthermore, it is shown that this new iteration method is equivalent to some other iteration methods in the sense of convergence. Finally, it is proved that this new iteration method is T-stable.
Keywords: MANN ITERATIONS; STABILITY; THEOREMS; EQUIVALENCE; ISHIKAWA; APPROXIMATION; CONVERGENCES; Mathematics